P1509SEVERITY OF PRURITUS IN HEMODIALYSIS PATIENTS: RELATIONSHIP TO UREMIC TOXINS AND DIALYSIS MODALITY. (6th June 2020) - Yamamoto, Suguru; Tanaka, Takahiro; Omori, Kentaro; Ei, Isei; Kitamura, Nobutaka; Narita, Ichiei
Abstract: Background and Aims: Pruritus is a complication that can impair the quality of life of patients with chronic kidney disease (CKD). A previous report has suggested that the severity of pruritus is correlated with high serum concentrations of β2 -microglobulin, calcium, and phosphorus, however recent developments in hemodialysis (HD), especially use of high-flux membrane and online hemodiafiltration (OLHDF), may improve the severity of pruritus. Protein-bound uremic toxins (PBUTs), such as indoxyl sulfate and p-cresyl sulfate, are known to be factors associated with atherosclerosis and impaired bone metabolism in CKD and may also be associated with pruritus, especially in those undergoing dialysis treatments. The aim of our study was to assess the severity of pruritus using a new tool, the 5D-itch scale (5D), as well as its relation to circulating PBUTs and dialysis modality in patients with end-stage kidney disease. Method: This was a prospective cohort multicenter study, wherein we analyzed the baseline data. The 5D score (5–25 points) was measured in maintenance dialysis patients. The serum concentrations of indoxyl sulfate, p-cresyl sulfate, phenyl sulfate and hippuric acid were measured with mass spectrometry before a dialysis session. The correlations of the 5D scores with serum PBUTs, dialysis modality (HD or OLHDF) and the other background factors were assessed with Spearman correlation coefficients and the generalized linear model. Results: This study included 135 dialysis patients (98 HD and 37 OLHDF). The mean 5D score was 6.84 (±SD 3.14). The mean serum concentrations of indoxyl sulfate, p-cresyl sulfate, indole acetic acid, phenyl sulfate, and hippuric acid were 2.99 ± 1.40, 2.05 ± 1.54, 0.11 ± 0.08, 0.94 ± 0.71, and 4.52 ± 3.17 mg/dL, respectively. There was a significant correlation between the 5D score and dialysis modality (correlation coefficient = 0.24, p < 0.01). Dialysis method was associated with the 5D score by the generalized linear model, and OLHDF was associated with a lower 5D score. There were no significant associations between the 5D score and serum concentrations of the various PBUTs (e.g., for indoxyl sulfate, the correlation coefficient was 0.11, p = 0.20) Conclusion: Pruritus, as assessed by the 5D score, was associated with dialysis modality, but not with the serum concentration of PBUTs. Further studies will be needed to understand the mechanism of the effect of OLHDF on pruritus as well as the role of uremic toxins in the itchy skin in CKD patients.